USING THE SPIRITUAL HERITAGE OF EASTERN THINKERS IN THE DEVELOPMENT OF AESTHETIC EDUCATION IN STUDENTS - Temirova, Matluba Karim kizi (Educational Research in Universal Sciences, 2024)
In this article, the role of the spiritual heritage of Eastern thinkers in the development of aesthetic education among elementary school students, that is, how important the spiritual heritage of our ancestors is in the process of improving aesthetic education among elementary school students, is the subject of the article. tried to reveal it as a problem.